2016
DOI: 10.21511/ppm.14(2).2016.05
|View full text |Cite
|
Sign up to set email alerts
|

Performance measurement by small and medium enterprises in Cape Metropolis, South Africa

Abstract: High failure rate of small and medium enterprises (SMEs) has been partly attributed to the use of inappropriate performance measures. This study seeks to determine the types of performance measures employed by SMEs, purpose for which performance measures are used, perceived effectiveness of performance measures used and factors that may inhibit SMEs from using both financial and non-financial performance measures. Data are collected using a questionnaire and analyzed using descriptive and inferential statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…For instance, a study by Vermaak, Kirsten and Wolmarans (2015) found that accountants in SMEs tend to depend on financial ratios more than the highly acclaimed Balanced Scorecard when measuring performance. Other studies conducted in South African SMEs (Dubihlela & Sandada, 2014;Epoh & Mafini, 2018;Maduekwe & Kamala, 2016;Mafini & Muposhi, 2017) applied subjective measures to determine the performance of these businesses. In line with these studies, the current research also applies subjective measures to quantify the performance of SMEs.…”
Section: Business Performancementioning
confidence: 99%
“…For instance, a study by Vermaak, Kirsten and Wolmarans (2015) found that accountants in SMEs tend to depend on financial ratios more than the highly acclaimed Balanced Scorecard when measuring performance. Other studies conducted in South African SMEs (Dubihlela & Sandada, 2014;Epoh & Mafini, 2018;Maduekwe & Kamala, 2016;Mafini & Muposhi, 2017) applied subjective measures to determine the performance of these businesses. In line with these studies, the current research also applies subjective measures to quantify the performance of SMEs.…”
Section: Business Performancementioning
confidence: 99%
“…Accordingly, the performance should be assessed from both financial and non-financial aspects. Financial performance for SMEs is usually evaluated through the following criteria: (i) growth in sales; (ii) growth in profits; and (iii) cash flow [26][27][28] . In addition, many enterprises also measure performance through non-financial indicators such as valued customer, employee conditions, and product/service development 27,29 .…”
Section: The Theoretical Framework For Performancementioning
confidence: 99%
“…Besides, non-financial performance offers insight into the link between business activities with financial results that considerably impact business performance and competitiveness. For example, the degree of customer satisfaction could indicate future cash flow that would otherwise not be available (Maduekwe & Kamala, 2016).…”
Section: Organizational Performancementioning
confidence: 99%